Resistance analysis of hepatitis C virus genotype 1 prior treatment null responders receiving daclatasvir and asunaprevir. Issue 3 (16th July 2013) - McPhee, Fiona; Hernandez, Dennis; Yu, Fei; Ueland, Joseph; Monikowski, Aaron; Carifa, Arlene; Falk, Paul; Wang, Chunfu; Fridell, Robert; Eley, Timothy; Zhou, Nannan; Gardiner, David
<x xml:space="preserve">Abstract</x> In a sentinel cohort, hepatitis C virus (HCV) patients (primarily genotype [GT] 1a) were treated with daclatasvir (NS5A inhibitor) and asunaprevir (NS3 protease inhibitor). Preexistence, emergence, and persistence of resistance variants in patients who failed this treatment are described. HCV‐infected null responders received daclatasvir (60 mg once daily) and asunaprevir (600 mg twice daily) alone (Group A, 11 patients) or with peginterferon alfa‐2a and ribavirin (Group B, 10 patients) for 24 weeks. Resistance testing was performed on baseline samples and samples with HCV RNA ≥1, 000 IU/mL at Week 1 through posttreatment Week 48. Resistance substitution susceptibility to inhibition by asunaprevir and daclatasvir was assessed using HCV replicon assays. In Group A, six GT1a patients experiencing viral breakthrough and one GT1a patient who relapsed had detectable NS5A (Q30E/R, L31V/M, Y93C/N) and NS3 (R155K, D168A/E/V/Y) resistance‐associated variants at failure. Two of six viral breakthrough patients achieved SVR48 after treatment intensification with peginterferon alfa‐2a and ribavirin. For 2/4 viral breakthrough patients not responding to treatment intensification, NS3 resistance variants changed (D168Y to D168T; R155K to V36M‐R155K). At posttreatment Week 48, daclatasvir‐resistant variants persisted while asunaprevir‐resistant variants were generally replaced by wild‐type sequences. The NS3 sequence remained unchanged in the one patient with NS3‐R155K at baseline, relapse, and posttreatment Week 48. In Group B, no viral breakthrough was observed. Conclusion: The treatment failure of daclatasvir and asunaprevir in HCV GT1a patients was associated with both NS5A and NS3 resistance variants in prior null responders. NS5A resistance variants persisted while NS3 resistance variants generally decayed, suggesting a higher relative fitness of NS5A variants. (Hepatology 2013;53:902–911)